Small molecules against B-RAF (BRAF) Val600Glu (V600E) single mutation - Zaharie F (Dove Medical Press, 2015)
Florin Zaharie,1,* Roxana Cojocneanu-Petric,1,* Mihai Muresan,1 Ioana Frinc,2 Delia Dima,2 Bobe Petrushev,3 Alina Tanase,4 Cristian Berce,1 Mariana Chitic,2 Ioana Berindan-Neagoe,1 Valentina Pileczki,1 Alexandru Irimie,5 Ciprian Tomuleasa2 1Iuliu Hatieganu University of Medicine and Pharmacy, 2Department of Hematology, Ion Chiricuta Oncology Institute, 3Department of Pathology, Emergency University Hospital, Cluj Napoca, 4Department of Stem Cell Transplantation, Fundeni Clinical Institute, Bucharest, 5Department of Surgery, Ion Chiricuta Oncology Institute, Cluj Napoca, Romania *These authors contributed equally to this communicationWe have read with great interest the paper by Tang and Chen1 published in the most recent issue of the International Journal of Nanomedicine, in which the authors describe the protocol by which scientists constructed the ideal BRAF (V600E)-modeled structure through homology modeling and introduced the method of structure-based docking or virtual screening from a large compound database. They concluded that BRAF (V600E) has a quite prominent structural or conformational variation when compared to the wild-type BRAF protein by matrix of root mean square fluctuation and principal component analysis. On the basis of structure-based virtual screening, ligand-based quantitative structure activity relationship models, and molecular dynamics simulation, we recommend aknadicine and 16beta-hydroxy-19s-vindolinine N-oxide as potent compounds for developing novel inhibitors in the future. Read the original article